Does Migration Motive Matter for Migrants' Employment Outcomes? The Case of Belgium - Dries Lens; Ive Marx; Suncica Vujic (Institute of Labor Economics (IZA), 2018)
Despite being one of the most prolific spenders on active labour market policies, and investing heavily in civic integration programmes, family policies and career and diversity plans, the native-migrant employment gap in Belgium is still one of the largest among EU and OECD countries. Past research has shown that even after controlling for human capital and other socio-demographic factors a large unexplained gap (often called ethnic gap or penalty) remains. This paper investigates how the motive for migrating to Belgium contributes to the native-migrant employment gap. Based on data from the 2014 Belgian LFS Ad Hoc Module on the labour market situation of migrants and their immediate descendants, we compare the employment outcomes of labour migrants (with and without a job prior to migration), family reunion migrants, student migrants and refugees with those of the native-born. In line with previous studies, we establish that refugees and family reunion migrants' employment likelihood is lower when compared to labour migrants and natives. Refugees who do work tend to do so in temporary jobs and in jobs that are below their skill levels. However, temporary employment is also prevalent among labour migrants without a job prior to migration and over qualification is a specific challenge for male student migrants.
Keywords: F22; J15; J61; 330; immigration; reason for migration; employment outcomes